2022
DOI: 10.1007/s00068-022-02203-7
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic retropharyngeal hematoma without spinal cord injury or spinal fracture: a retrospective multicenter analysis

Abstract: Background Retropharyngeal hematoma can be a life-threatening injury due to progressive upper airway obstruction. It is common following spinal cord injury or spinal fracture, and the clinical course and outcome of such patients are determined by their primary injuries. However, the natural clinical course of retropharyngeal hematoma itself remains unclear. In this study, we aimed to examine the clinical characteristics of traumatic retropharyngeal hematoma without spinal cord injury or spinal fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 20 publications
(27 reference statements)
1
11
0
Order By: Relevance
“… 11 , 32 , 73 This was similar to the median diameter of the hematoma in the intubated cases in Shiba study. 88 These results confirm the predictive value of hematoma size in predicting the need for early intubation. Therefore, a large hematoma on sagittal CT images should be considered a red flag for early intubation.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“… 11 , 32 , 73 This was similar to the median diameter of the hematoma in the intubated cases in Shiba study. 88 These results confirm the predictive value of hematoma size in predicting the need for early intubation. Therefore, a large hematoma on sagittal CT images should be considered a red flag for early intubation.…”
Section: Discussionsupporting
confidence: 66%
“…Those receiving anticoagulants or those with coagulation disorders are at an increased risk of bleeding. 88 An additional study carried out by Shiba et al 88 indicated similar results with a median age of 69 and a male dominance distribution. It was also found in the same study by Shiba et al, 88 that high bleeding was associated with international normalized ratio of 4.5 and above.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations